Transoral thyroidectomy implemented by a novice surgeon: Efforts for safe implementation. Issue 1 (1st December 2022) - Lee, Dong Won; Kim, Jeong Kyu; Shin, Seung Heon; Tae, Kyung
Abstract: Background: This study aimed to evaluate the feasibility, safety, and early surgical outcomes of transoral robotic and endoscopic thyroidectomy conducted by a novice surgeon. Methods: We analyzed 27 patients who underwent transoral thyroidectomy between December 2018 and November 2021. All the surgeries were performed by a novice surgeon without prior endoscopic or robotic surgery experience; the surgeon had experienced 12 cases of transcervical thyroidectomy before adopting transoral thyroidectomy. Results: Of the 27 cases, 1 was converted to the transcervical approach due to poor bleeding control. Four cases had transient recurrent laryngeal nerve palsy, and three had transient hypoparathyroidism. Most of the patients were very satisfied with the postoperative cosmetic outcome. Conclusions: Transoral robotic and endoscopic thyroidectomies are feasible for the novice surgeon, with reasonable results in the early adoption stage if preparations are according to the suggested framework. Level of Evidence: Level 4. Abstract : This study aimed to evaluate the feasibility, safety, and early surgical outcomes of transoral robotic and endoscopic thyroidectomy conducted by a novice surgeon. Transoral robotic and endoscopic thyroidectomies are feasible for the novice surgeon, with reasonable results in the early adoption stage if preparations are according to the suggested framework.